Análises moleculares de populações de Wasmannia auropunctata Roger, 1863 (Hymenoptera: Formicidae) e da presença de endossimbiontes - Silva, Larissa Marin Rodrigues [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Wasmannia auropunctata is a generalist ant, native of the Neotropical region that has being spread in worldwide scale and when introduced in new areas, many times by human transportation, can cause environmental, economics and health service troubles. Control alternatives and differences between introduced and native populations as well as between clonal and sexual colonies, has increased the interest about this species. The endosymbiont Wolbachia, the most widespread between arthropods, is responsible for many reproductive manipulations in its hosts and has been considered as a possibility of control agent for several species. Thus, the aim of this work was better understand the relationship between these two organisms and increase the molecular profiles of populations in South America. For this purpose, workers of 31 collection points were analyzed by PCR amplification and Sanger s sequencing of the nuclear (28S rDNA) and mitochondrial (COI, IGS, tRNA e COII) genes, as well as wsp and coxA genes from the endosymbiont. The molecular characterization of workers and their endosymbionts and the Network analysis from both showed that there is evidences for believe that: the Leu-tRNA and the IGS between the COI and COII genes could be used to help in the inter and intraspecific distinction of these ants, respectively; the region of 28S rDNA should not be used alone as a marker to the identification of these ants; the samples that presented shorter IGS could represent ancient populations; natural dispersal and human transportation are likely to be occurring between the samples screened; the coxA gene is more appropriate than the wsp gene for detection of Wolbachia in this ants; vertical and horizontal transmission of the endosymbiont can be occurring; two of the alleles found in this work may be involved in ants specialization. Although this work brings new data and interesting hypothesis, more studies are needed to achieve a better...

Wasmannia auropunctata é uma espécie de formiga generalista e nativa da região Neotropical que tem se dispersado mundialmente. Quando introduzida em novas áreas, muitas vezes por ação antrópica, pode causar problemas ambientais, econômicos e de saúde pública. Diferenças encontradas entre populações introduzidas e nativas, ou sexuais e clonais tem aumentado o interesse por essa espécie, assim como alternativas para seu controle. O endossimbionte Wolbachia, além de ser amplamente distribuído entre os artrópodes e ser responsável por causar alterações reprodutivas em seus hospedeiros, tem sido considerado como um possível agente de controle para diversas espécies. Buscando compreender melhor a relação existente entre esses dois organismos e aumentar os perfis moleculares de populações na América do Sul, operárias de W. auropunctata de 31 pontos de coleta provenientes do Brasil e da Colômbia foram analisadas através da amplificação por PCR e sequenciamento de Sanger dos genes nuclear (28S rDNA) e mitocondrial (COI, IGS, tRNA e COII), assim como do gene wsp e coxA do endossimbionte. Através da caracterização molecular das operárias e de seus endossimbiontes e da análise das redes de haplótipos para ambos, observou-se que há evidências de que: o Leu-tRNA e o IGS entre o COI e COII podem ser utilizados para auxiliar na diferenciação inter e intraespecífica, respectivamente; o fragmento do gene 28S rDNA utilizado neste trabalho não deve ser utilizado sozinho para a identificação dessas formigas; amostras que apresentam IGS menor representam uma linhagem mais antiga; dispersão natural e por ação antrópica podem ter ocorrido entre as amostras analisadas; o gene coxA é o mais indicado para a detecção de Wolbachia nessas formigas do que o gene wsp; transmissão vertical e horizontal do endossimbionte são passíveis de estarem ocorrendo; dois dos alelos encontrados para o gene coxA podem estar envolvidos na
Keywords: Ants; Formiga; Inseto - Controle; Genetica animal; Formiga - Aspectos moleculares